MODERN TREATMENT OF METASTATIC MELANOMA: FROM STANDARDS TO AN INDIVIDUALIZED APPROACH IN REAL CLINICAL PRACTICE - N. V. Zhukova; R. V. Orlova; N. Yu. Antimonik; S. I. Kutukova; N. P. Belyak; N. V. Popova; S. P. Erdniev (Исследования и практика в медицине)
The incidence and mortality of skin melanoma in the world and in Russia is growing every year. It should be noted that the proportion of patients with melanoma of late stages remains high. Until recently, only ineffective chemotherapy regimens were available for such patients. That is why the possibility of using modern drugs in real clinical practice for the treatment of this cohort of patients is an urgent issue of modern clinical oncology. The appearance in a real clinical practice of a new group of immunological drugs (anti-CTLA4 and anti-PD-1) for the treatment of patients with metastatic melanoma allows to increase both the time to progression and the life span of this cohort of patients.In this article, we present the experience of St. Petersburg Regional Clinical Hospital “City Clinical Oncology Clinic” in the treatment of patients with metastatic melanoma under the conditions of real clinical practice with the preparation of ipilimumab as part of the expanded access program from February 2014 to March 2017. In total, 31 patients with disseminated melanoma (12 men and 19 women) were treated with ipilimumab during this period. The average age was 57 years (from 39 to 81 years), in 8 patients there were metastases to the brain. Patients with ECOG status 1 at the time of initiation of treatment were the majority 28 patients (90%), three patients (10%) had ECOG status 2. All patients had previously received 1 to 4 lines of systemic chemotherapy. The median of the observation period is currently 12 (3-35) months. The median time to progression was 6 months. At 5 of 31 patients at the time of analysis, signs of progression were not identified. The median overall survival (OB) was 12 months 9 of 31 patients were alive at the time of the analysis. The annual OM was 56.5%, the 2-year period was 29.4%.The article presents a clinical case of treatment of a patient with metastatic melanoma, which will have an effect against the progression of the disease after four lines of therapy, including ipilimumab. The patient was included in the program of expanded access to the PD-1 inhibitor, nivolumab. In all, the patient received 65 nivolumab injections. The life expectancy of the patient from the moment of diagnosing the metastatic stage of the disease is 3.5 years, while 2.5 years on the background of nivolumab therapy. Patient monitoring continues.